2020
DOI: 10.1038/s41564-020-0691-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial alginate regulators and phage homologs repress CRISPR–Cas immunity

Abstract: CRISPR-Cas systems are adaptive immune systems that protect bacteria from bacteriophage (phage) infection 1 . To provide immunity, RNA-guided protein surveillance complexes recognize foreign nucleic acids, triggering their destruction by Cas nucleases 2 . While the essential requirements for immune activity are well understood, the physiological cues that regulate CRISPR-Cas expression are not. Here, a forward genetic screen identifies a two-component syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 50 publications
1
37
0
Order By: Relevance
“…Thus, the regulation of defense systems including CRISPR-Cas on the one hand and new DNA acquisition mechanisms including natural competence systems on the other hand is extremely important for bacterial adaptation to changing environments with fitness cost considerations. Recent studies provided new examples of such regulatory mechanisms involving sRNAs under the control of TCS in major pathogens [ 64 , 157 , 158 , 159 , 160 , 161 ].…”
Section: Srnas Regulating Host-pathogen Interactionsmentioning
confidence: 99%
“…Thus, the regulation of defense systems including CRISPR-Cas on the one hand and new DNA acquisition mechanisms including natural competence systems on the other hand is extremely important for bacterial adaptation to changing environments with fitness cost considerations. Recent studies provided new examples of such regulatory mechanisms involving sRNAs under the control of TCS in major pathogens [ 64 , 157 , 158 , 159 , 160 , 161 ].…”
Section: Srnas Regulating Host-pathogen Interactionsmentioning
confidence: 99%
“…Of note, cells had to be grown to high cell density, which is important for Cas protein expression in P. aeruginosa (Fig. 1b) (Høyland-Kroghsbo et al, 2017;Borges et al, 2020). Analysis of fluorescent signal from single cells indicated that Csy1 and Csy4 protein levels are higher than Cas3 (Fig.…”
Section: Establishing Reporter Systems For Live Cell Visualization Ofmentioning
confidence: 99%
“…Endogenous Csy1-sfCherry and Cas3-sfCherry reporters were previously described (Borges et al, 2020). Csy4-sfCherry was constructed in a similar way.…”
Section: Construction Of Plasmids and Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…How are CRISPR systems regulated within their bacterial hosts to prevent autoimmunity and enhance targeting of foreign agents? Several studies have demonstrated transcriptional and post-transcriptional CRISPR-Cas regulation in response to extracellular and intracellular cues 20 , including phage infection [21][22][23][24][25] , quorum sensing 26,27 , membrane stress [28][29][30][31] , metabolic status 21,32,33 and surface association 34 . In many cases where the regulatory mechanisms are known, host-encoded transcription factors interact with CRISPR-Cas promoters 32,33,35,36 , although several studies have shown that archaeal type I-A systems can be intrinsically controlled by dedicated Cas-encoded transcription factors 25,[37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%